2017
DOI: 10.1159/000480317
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Mesenchymal Stem Cells Rescue Myocardial Ischaemia/Reperfusion Injury by Inducing Cardiomyocyte Autophagy Via AMPK and Akt Pathways

Abstract: Background/Aims: Reperfusion after an ischaemic insult might cause infarct extension. Mesenchymal stem cell (MSC)-derived exosomes could attenuate myocardial remodelling in animal models of myocardial ischaemia reperfusion injury (MIRI), and the present study aimed to explore the related mechanisms. Methods: In vitro, rat H9C2 cardiomyocytes (H9C2s) were exposed to H2O2. Cell viability was detected by the CCK-8 assay, apoptosis was detected by Annexin V-PE/7-AAD staining, ROS production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
189
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(193 citation statements)
references
References 45 publications
4
189
0
Order By: Relevance
“…Previous investigations have suggested that mTOR is inhibited during energy insufficiency, which subsequently stimulates autophagy. During myocardial ischemia or R/I ischemia/ reperfusion injury in vivo and in vitro, the AMPK/mTOR pathway is activated [38,39]. Our results revealed that Pim1 upregulated autophagy after hypoxia and H 2 O 2 , partly because of activation of the AMPK/mTOR/ATG5 autophagy pathway.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 68%
“…Previous investigations have suggested that mTOR is inhibited during energy insufficiency, which subsequently stimulates autophagy. During myocardial ischemia or R/I ischemia/ reperfusion injury in vivo and in vitro, the AMPK/mTOR pathway is activated [38,39]. Our results revealed that Pim1 upregulated autophagy after hypoxia and H 2 O 2 , partly because of activation of the AMPK/mTOR/ATG5 autophagy pathway.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 68%
“…Exosomes (Exos) derived from MSCs have been described as a novel pathway of cell-to-cell interaction and a crucial point in signal regulation [21][22][23]. These membranous structures which deliver exogenous functional mRNA and miRNA sequences to target cells contribute to disease progression and can help to treat diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine monophosphate-activated protein kinase (AMPK) has emerged as a master regulator of metabolic energy, and is a cellular adaptive mechanism activated during metabolic stress to boost energy production and so that to salvage the failing myocardium [13, 14] and myocardial IR injury [15]. Of note, AMPK activation has been verified to confer cardioprotection against myocardial IR injury in diabetes by limiting cardiac apoptosis through attenuation of endoplasmic reticulum stress [14, 16].…”
Section: Introductionmentioning
confidence: 99%